2020
DOI: 10.1111/ijd.15032
|View full text |Cite
|
Sign up to set email alerts
|

Significance of SOX18 expression in nonmelanoma skin cancers for prediction of high‐risk patients: a preliminary study

Abstract: Background SOX18 is an integral transcription factor that is involved in endothelial cells differentiation during both angiogenesis and lymphangiogenesis. Therefore, it has been implicated in tumor progression and metastasis. Objective To study SOX18 expression in nonmelanoma skin cancers (NMSCs) in comparison to seborrheic keratosis (SK) and normal control skin, and to assess its probable role in tumor evolution and progression. Patients and Methods This study was conducted on 60 specimens of NMSCs: 30 basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Two different studies [ 40 , 41 ] indicated that SOX18, a transcription factor involved in endothelial cell differentiation, was upregulated in skin cancers whereas it was nearly absent in healthy skin samples. Neinaa et al [ 40 ] showed that the level of SOX18 was higher in cSSC lesions with a significant difference from actinic keratoses.…”
Section: Literature Search Strategy and Yielded Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different studies [ 40 , 41 ] indicated that SOX18, a transcription factor involved in endothelial cell differentiation, was upregulated in skin cancers whereas it was nearly absent in healthy skin samples. Neinaa et al [ 40 ] showed that the level of SOX18 was higher in cSSC lesions with a significant difference from actinic keratoses.…”
Section: Literature Search Strategy and Yielded Resultsmentioning
confidence: 99%
“…The results found for SOX18 could indicate a possible role for this transcription factor in the malignancy and aggressiveness of the tumor, given that it is not found in healthy skin and is found in lesser quantities in benign tumors such as actinic keratoses than in malignant tumors such as cSCC. Furthermore, the vessel density was higher in samples with more intensity of SOX18 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neinaa YME et al compared skin tumor with healthy skin tissue by immunohistochemical staining, and significant SOX18 overexpression was observed in cutaneous tumors in SCC and BCC. [ 40 ]. Early events of BCC tumorigenesis are triggered by inappropriate activation of SHH signaling.…”
Section: Discussionmentioning
confidence: 99%